2021
DOI: 10.1016/j.foodres.2021.110115
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic evidence for pectin changes in hard-to-cook development of common beans during storage

Abstract: Microscopic evidence for pectin changes in hard-to-cook development of common beans during storage,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In this regard, more research coupled with quantification analysis of the constituents involved such as pectic substances, phenolic substances, and cations is needed. In a recent microscopy study, Chen et al (2021) concluded that there is a possible contribution of both the pectin-cation-phytate hypothesis and the involvement of pectin crosslinks in HTC development in the cotyledon during storage of red haricot It is suggested that the cooking quality of beans can be maintained during storage under specific conditions of low temperature (<25 • C) and low relative humidity (<65%). In this context, the glass transition (T g ) theory has been described in the literature as a concept to explain food stability in relation to molecular mobility of reacting components in the matrix.…”
Section: Postharvest Storage Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, more research coupled with quantification analysis of the constituents involved such as pectic substances, phenolic substances, and cations is needed. In a recent microscopy study, Chen et al (2021) concluded that there is a possible contribution of both the pectin-cation-phytate hypothesis and the involvement of pectin crosslinks in HTC development in the cotyledon during storage of red haricot It is suggested that the cooking quality of beans can be maintained during storage under specific conditions of low temperature (<25 • C) and low relative humidity (<65%). In this context, the glass transition (T g ) theory has been described in the literature as a concept to explain food stability in relation to molecular mobility of reacting components in the matrix.…”
Section: Postharvest Storage Conditionsmentioning
confidence: 99%
“…In a recent microscopy study, Chen et al. (2021) concluded that there is a possible contribution of both the pectin‐cation‐phytate hypothesis and the involvement of pectin crosslinks in HTC development in the cotyledon during storage of red haricot…”
Section: Factors Influencing Bean Cooking Timesmentioning
confidence: 99%
“…That is, the type of reactions and relative rate of reactions for different types of foods were better related with a w than with moisture content. Thus, in the food literature, storage experiments often refer to a w or storage RH (e.g., Fu et al, 2020 ; Chen et al, 2021 ; Zhao et al, 2021 ), and/or involve the determination of isotherms (e.g., Staniszewska et al, 2020 ; Rosa et al, 2021 ). When the temperature of the sample is below the relevant glass transition threshold (see below), reliable detection of a w is not possible, while an apparent RH may still be detected (Schiraldi et al, 2012 ).…”
Section: What Are Moisture Sorption Isotherms and Why Are They Inform...mentioning
confidence: 99%
“…Previous studies aiming to understand the HTC defect relied on the physical, chemical, and ultrastructural comparison of fast- and slow-cooking beans, in which the changes in the cell wall have been extensively studied [ 19 , 23 , 24 , 25 , 26 ]. Breeding studies have utilized quantitative trait loci (QTL) mapping and genome-wide association studies (GWAS) to identify chromosomal regions on P. vulgaris associated with cooking time.…”
Section: Introductionmentioning
confidence: 99%